MARIA IZILDA SANTOS DE MATOS: MEMORIES, STORIES AND INTELLECTUAL TRAJECTORY - Reznik, Luís; Gonçalves, Paulo Cesar [UNESP]; Fernandes, Rui Aniceto Nascimento (Pontifical Catholic University of Sao Paulo (PUC-SP), 2022)
The interview conducted with Maria Izilda Santos de Matos records the life and intellectual trajectory of the teacher and researcher, daughter of Portuguese immigrants, highlighting memories, histories, research, theoretical-methodological assumptions, and contributions related to the theme of e/immigration. In the beginning, she recovers her family memory, her childhood studies in São Paulo, the option for History as a career in teaching, the student experience at the USP, the choice for postgraduate studies, the conciliation between teaching and research. Afterwards, she reconstructs her academic path as a professor at PUC/SP and her participation in development agencies and in the formation of national and international research groups, commenting on her important work, and how the studies on e/immigration were incorporated to its universe of investigation.
MARIA IZILDA SANTOS DE MATOS: MEMÓRIAS, HISTÓRIAS E TRAJETÓRIA INTELECTUAL
Keywords: Intellectual trajectory; Memory; Migratory Studies